2023
DOI: 10.1038/s41568-023-00584-4
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome immaturity and childhood acute lymphoblastic leukaemia

Abstract: Acute lymphoblastic leukaemia (ALL) is the most common cancer of childhood. Here, we map emerging evidence suggesting that children with ALL at the time of diagnosis may have a delayed maturation of the gut microbiome compared with healthy children. This finding may be associated with early-life epidemiological factors previously identified as risk indicators for childhood ALL, including caesarean section birth, diminished breast feeding and paucity of social contacts. The consistently observed deficiency in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 148 publications
1
13
0
Order By: Relevance
“…In this register-based cohort study, we found that longer duration of exclusive breastfeeding (ie, for a period of at least 3 months) was associated with reduced risk of childhood BCP-ALL. This finding is consistent with emerging investigations implicating early gut microbiome maturation in childhood BCP-ALL pathogenesis . To inform future preemptive interventions, additional studies should investigate the biologic mechanisms underlying the observed association.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In this register-based cohort study, we found that longer duration of exclusive breastfeeding (ie, for a period of at least 3 months) was associated with reduced risk of childhood BCP-ALL. This finding is consistent with emerging investigations implicating early gut microbiome maturation in childhood BCP-ALL pathogenesis . To inform future preemptive interventions, additional studies should investigate the biologic mechanisms underlying the observed association.…”
Section: Discussionsupporting
confidence: 87%
“…This finding is consistent with emerging investigations implicating early gut microbiome maturation in childhood BCP-ALL pathogenesis. 16,17,30…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations